The Tail That Wags the Dog: How the Disordered C-Terminal Domain Controls the Transcriptional Activities of the p53 Tumor-Suppressor Protein. Issue 12 (December 2016) - Laptenko, Oleg; Tong, David R.; Manfredi, James; Prives, Carol
Abstract : The p53 tumor suppressor is a transcription factor (TF) that exerts antitumor functions through its ability to regulate the expression of multiple genes. Within the p53 protein resides a relatively short unstructured C-terminal domain (CTD) that remarkably participates in virtually every aspect of p53 performance as a TF. Because these aspects are often interdependent and it is not always possible to dissect them experimentally, there has been a great deal of controversy about the CTD. In this review we evaluate the significance and key features of this interesting region of p53 and its impact on the many aspects of p53 function in light of previous and more recent findings. Trends: p53 is a TF that exerts its antitumor activity predominantly through the transcriptional regulation of multiple target genes. Rapid identification of cognate p53 sites within the chromatin context of the eukaryotic cell, stable sequence-specific DNA binding, and cofactor recruitment are vital for an accurate and efficient transcriptional outcome mediated by p53 in response to a variety of stimuli of exogenous and endogenous nature. The intrinsically disordered CTD participates in all aspects of p53 functioning as a TF. Lack of structural constraints, conformational dynamics, and a unique amino acid composition are important for functions of the CTD within p53. Despite the current lack of structural information on the CTD within p53, the CTD is an integral part of the tetramer and participates in its binding-induced structural changes.